Answer:
36 is the final value for the equation you posted
Step-by-step explanation:
We are told that = 3 and = −2.
Let's plug these values into the equation.
= (5 ( − 2) + (2 − )^2)
= (5 (3 − 2(−2)) + (2 − 3)^2)
= (5 (3 + 4) + (−1)^2)
= (5 (7) + 1)
= 35 + 1
= 36
Answer:
![\boxed{\sf \dfrac{41}{63}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Csf%20%5Cdfrac%7B41%7D%7B63%7D%7D)
Step-by-step explanation:
hi, it means that we have to compute
![\dfrac{2}{9}+\dfrac{3}{7}=\dfrac{7*2+3*9}{7*9}=\dfrac{14+27}{7*9}=\dfrac{41}{63}](https://tex.z-dn.net/?f=%5Cdfrac%7B2%7D%7B9%7D%2B%5Cdfrac%7B3%7D%7B7%7D%3D%5Cdfrac%7B7%2A2%2B3%2A9%7D%7B7%2A9%7D%3D%5Cdfrac%7B14%2B27%7D%7B7%2A9%7D%3D%5Cdfrac%7B41%7D%7B63%7D)
(x-6)(x+2)
When you foil it you get x^2+2x-6x-12
After you do this you then add like terms to get x^2-4x-12
Therefore the answer (x-6)(x+2) is correct.
Hello!
The Correct Answer for this Question would be:
"<span>Start with 10.5. Add 3.5 and 10.5. Add 2.25 to the sum. Then add 5 to the answer."
In Other Words, Option "B".
Hope this Helps! Have A Wonderful Day! :)</span>